The effect of ball spin rate on distance achieved in a long soccer throw-in - Linthorne, N. P.; Thomas, J. M. (Procedia Engineering, 2016)
In this study a skilled soccer player performed throws for maximum distance while manipulating the backspin on the ball. A video analysis was used to obtain measures of the ball projection variables. We found that putting greater backspin on the ball did not reduce the player's ability to produce a high projection velocity. Throw distance increased at a rate of about 0.6 m per 1 rev/s increase in backspin, and the experimental data was consistent with the predictions of a mathematical model. We recommend players apply the highest possible backspin when performing a long throw-in.